White Space and Dark Matter: Prying Open the Black Box of STS. (March 2018) - Mascarenhas, Michael
To a packed audience in Clark Hall, Sheila Jasanoff, a distinguished scholar and former president of the Society for Social Studies of Science (4S), gave the plenary address for "Where has STS Traveled, " a commemorative gathering of the fortieth anniversary of the inaugural meeting of the 4S. Not only was this meeting located in the very same (renovated) room as the first gathering, but also many of the original members had traveled from far and wide to Cornell University to reminisce and reflect on the academic field they had established, as well as imagine the possibilities of the next forty years. In response to a question about the direction of STS, Professor Jasanoff suggested that the 4S had not turned its reflective gaze inward to examine the politics of its own society, nor had it spent much effort interrogating the society's contribution to social policy or enduring social problems. As I heard Jasanoff speak about our collective need for reflection and reflexivity, I had to wonder whether, and to what extent, we were ready to reflect on the subject matter of race and racism in this mostly color-blind field of inquiry.